Pengaruh Rasio Keuangan Terhadap Pertumbuhan Laba Perusahaan Jasa Komunikasi Dengan Firm Size Sebagai Moderasi - Karno, Karno (Owner : Riset dan Jurnal Akuntansi, 2024)
The purpose of this study was to find empirical evidence regarding the effect of financial ratios proxied by CR, ROA, TATO, and NPM on earnings growth with Company Size as a moderating variable in communication service companies listed on the IDX for the period 2018-2022. This research is a quantitative study with research samples taken from OSIRIS datavase. The sample selection in this study used purposive sampling technique, as for the criteria set were (1) listing on the IDX in the communication services sector consistently for five years from 2018-2022, and (2) no missing data, from this process 19 companies were obtained from 43 companies with the final observation sample obtained, namely 95 research data. This study found that Current ratio (CR) and Net Profit Margin (NPM) has a affect on profit growth, while Return on assets (ROA) and Total Assets Turnover (TATO) have no effect on the profit growth of communication service companies listed on the IDX for the 2018-2022 period. Meanwhile, company size is unable to moderate the effect of current ratio, return on assets, total assets turnover, and net profit margin on earnings growth. The contribution of this research is to provide empirical evidence regarding the effect of financial ratios proxied by CR, ROA, TATO, and NPM on profit growth with Company Size as a moderating variable in communication service companies listed on the IDX for the 2018-2022 period.